2019
DOI: 10.2528/pierm19060501
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Dual-Band Dual-Squarering (Dsr) Based Microstrip Antenna for Wifi/Wlan and 5g-Nr Wireless Applications

Abstract: In this work, a compact planar dual-square ring (DSR) microstrip patch antenna is investigated to acquire dual-band resonance with dual-mode excitation for Wi-Fi/WLAN and 5G-NR based wireless applications. This dual-square ring geometry is employed on single layer dielectric, excited through EM coupling by using a quadrilateral feed patch, which offers massive flexibility in impedance matching for dual-band resonance with minimum coupling effects in common excitation and ground plane. This planar DSR structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The two bands with the desired bandwidth can be easily obtained. All other antenna structures [5,6,14,[17][18][19][20]22] have larger dimensions than the proposed antennas. The proposed structures have neither any complex SRR nor meta-material, and thus, the proposed antennas are simple to design.…”
Section: Comparison With State Of Art Antennasmentioning
confidence: 97%
See 2 more Smart Citations
“…The two bands with the desired bandwidth can be easily obtained. All other antenna structures [5,6,14,[17][18][19][20]22] have larger dimensions than the proposed antennas. The proposed structures have neither any complex SRR nor meta-material, and thus, the proposed antennas are simple to design.…”
Section: Comparison With State Of Art Antennasmentioning
confidence: 97%
“…Multiband antennas using annular ring and meta-material inspired split-ring resonator (SRR) are designed in [14][15][16][17][18][19][20][21][22]. An elliptical-ring with a split-triangular patch [14] and two connected rings [15] are used in designing a flexible dual-band and a transparent tri-band antenna, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many designs had been presented for patch antenna operating for 5G applications at S-Band, where a patch antenna was printed on an FR4 material with two pin diodes used to initiate a single mode of operating for each diode and has an operating frequency of 3.6 GHz [13]. A patch antenna with doubled square ring was proposed to operate at 3.7 GHz for 5G use [14]. Multiple input multiple output (MIMO) antennas had been proposed for 5G applications with frequency of 3.41 GHz and gain of 4.2 dB [15].…”
Section: Introductionmentioning
confidence: 99%
“…From Table 1, it is shown that different countries have allocated different sub-6 GHz bands ranging from 3.3 GHz to 5 GHz. The above-mentioned frequency bands have been intensively studied in some previous works [7][8][9][10][11][12]. Note that the 5.0-5.5 GHz, which is part of , is not adopted in the most countries for a while, but it is considered as an important spectrum for the future development of 5G applications [13,14].…”
Section: Introductionmentioning
confidence: 99%